Mycobacterial Infections in AIDS - A Ross Hill (Canadian Journal of Infectious Diseases)
Tuberculosis (TB) remains uniquely important among acquired immune deficiency syndrome (AIDS)-associated opportunistic infections: it presents the greatest public health hazard worldwide, is the most readily curable, and is largely preventable with existing means. Given the expanding pool of human immunodeficiency virus (HIV) seropositive persons, particularly in developing nations where Mycobacterium tuberculosis remains a leading health problem, one can expect a continued rise in TB cases during the 1990s. Global efforts to eliminate TB are now inextricably entwined with the effectiveness of measures to curtail the HIV epidemic. Mycobacterium avium complex infection, currently an intractable late complication of aids, may increase in clinical importance as success in managing other opportunistic infections and HIV disease itself improves. Understanding of the pathogenesis and management of mycobacterial diseases should increase rapidly given the renewed research spurred on by the advent of HIV.